Karl Theodor Jasper's Godhead Philosophy and Its Relevance for The Development of Religiousity Thought in Indonesia - Ushuluddin, Win; Furqon, Al (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2018)
This paper is aimed at analyzing Jaspers' Godhead philosophy, and finding the relevance of Jaspers’ Godhead philosophy for the development of religiousity thought in Indonesia. The material object of this paper is Jaspers' thought of divinity, and its formal object is philosophy of divine. There are four important terms in Jaspers' Godhead philosophy, namely: Transcendence, cipher, das Umgreifende, and philosophical faith. The terms Transcendence, cipher, das Umgreifende are express that human inability to perceive the true God, while the term ‘philosophical faith’ is the implication of his thinking about the divinity. Jaspers’ divinity thought is relevant to religious life in Indonesia, especially when interpreting the purpose of his philosophy that wants to restore humans to himself, namely: a man who has a clear way of life, so that he understands the meaning of his life. Jaspers' Godhead philosophy can be a criticism for a real effort to improve oneself to be whole and actual human beings; equal before God, despite that heterogeneous and plural fact of human life is a latent necessity, but not a reason for ignoring the existence of others, even attacking others, because heterogeneity and plurality are gift from God. Therefore, everyone is equally required to respect the values and world views of the others, even challenged and should try to understand other cultures and be tolerant to the practice of others.